Tempting to Tag: An Experimental Comparison of Four Tagging Input Mechanisms - Melenhorst, Mark; Velsen, Lex (Human Technology, 2010)
Tagging helps achieve improved indexing and recommendation of resources (e.g., videos or pictures) in large data collections. In order to reap the benefits of tagging, people must be persuaded to label the resources they consume. This paper reports on a study in which four different tagging input mechanisms and their effect on users' motivation to tag were compared. The mechanisms consisted of a standard tag input box, a chatbot-like environment, a bookmarking mechanism, and a "tag and vote" game. The results of our experiment show that the use of the nonstandard tagging input mechanisms does not affect users' motivation to tag. In some instances tagging mechanisms were found to distract users from their primary task: consuming resources. Persuading people to tag might be accomplished more effectively by using other motivating tagging mechanisms (e.g., tagging games), or motivation could be created by explaining the usefulness of tagging.